Thinking Collectively : Social Policy, Collective Action and the Common Good - Spicker, Paul (Book collections on Project MUSE., 2019)
"What does collectivism mean in social policy? What does thinking collectively imply for policy? In this book, well-respected author Paul Spicker lends a complementary voice to his book, reviewing collectivism as a dimension of political discourse. Breaking down his analysis to examine collectivism through substantive, moral and methodological lenses, he reviews a series of arguments for cooperative effort, solidarity and collective responsibility. Taking a dispassionate and methodical approach, the author explores what collectivism means in social policy and what value it offers to the field."--